Exploring the Impact of Zoning Education and Teacher Performance on Student Success in Kendari's Senior High Schools - Masdin Masdin; Karim Karim (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: This research investigates the interplay between the educational zoning system, teacher performance, and student academic achievement in high schools. Given the increasing implementation of zoning policies in Indonesia’s education system, understanding their direct and combined effects on teacher performance and student outcomes is critical for shaping equitable and adequate education policies. Methodology: The study focuses on six high schools in Kendari City, employing a quantitative approach to analyze the relationships between zoning policies, teacher performance, and student achievement. Data were collected through surveys and analyzed using statistical tests, including multiple regression analysis, with a significance threshold of α = 0.05. Main Findings: The results indicate that the educational zoning system positively and significantly impacts student academic outcomes, with a significance value and a contribution of 10.00%. Similarly, teacher performance significantly influences student achievement, with a significance value and a contribution of 10.00%. However, the zoning system does not directly affect teacher performance, as indicated by a non-significant, contributing only 3.4%. When combined, the zoning system and teacher performance significantly influence student achievement (ρ = 0.001), underscoring the complementary nature of policy and teacher effectiveness in improving academic performance. Novelty/Originality of the Study: This study provides new insights into the nuanced relationship between zoning policies and education quality, emphasizing the critical role of teacher performance in mediating policy outcomes and highlighting the importance of integrating zoning reforms with teacher development programs to maximize their collective impact on student achievement.